Numerical study on graphene nanoribbon quantum well-in-well interband and intersubband photodetector - Saha, Atanukumar; Saha, Gobinda; Rashid, A.B. M Harun Ur (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 15th IEEE International Conference on Nanotechnology, IEEE-NANO 2015; Rome; Italy; 27 July 2015 through 30 July 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/NANO.2015.7389010